[RETRACTED ARTICLE] Schizandrin A exerts anti-tumor effects on A375 cells by down-regulating H19 - Bi,Yiming (2019)
Malignant melanoma (MM) is one of the malignant tumors with highly metastatic and aggressive biological actions. Schizandrin A (SchA) is a bioactive lignin compound with strong anti-oxidant and anti-aging properties, which is stable at room temperature and is often stored in a cool dry place. Hence, we investigated the effects of SchA on MM cell line A375 and its underlying mechanism. A375 cells were used to construct an in vitro MM cell model. Cell viability, proliferation, apoptosis, and migration were detected by Cell Counting Kit-8, BrdU assay, flow cytometry, and transwell two-chamber assay, respectively. The cell cycle-related protein cyclin D1 and cell apoptotic proteins (Bcl-2, Bax, cleaved-caspase-3, and cleaved-caspase-9) were analyzed by western blot. Alteration of H19 expression was achieved by transfecting with pEX-H19. PI3K/AKT pathway was measured by detecting phosphorylation of PI3K and AKT. SchA significantly decreased cell viability in a dose-dependent manner. Furthermore, SchA inhibited cell proliferation and cyclin D1 expression. SchA increased cell apoptosis along with the up-regulation of pro-apoptotic proteins (cleaved-caspase-3, cleaved-caspase-9, and Bax) and the down-regulation of anti-apoptotic protein (Bcl-2). Besides, SchA decreased migration and down-regulated matrix metalloproteinases (MMP)-2 and MMP-9. SchA down-regulated lncRNA H19. Overexpression of H19 blockaded the inhibitory effects of SchA on A375 cells. SchA decreased the phosphorylation of PI3K and AKT while H19 overexpression promoted the phosphorylation of PI3K and AKT. SchA inhibited A375 cell growth, migration, and the PI3K/AKT pathway through down-regulating H19.